THE EFFECT OF PROFITABILITY AND CAPITAL STRUCTURE USING INFLATION AS MODERATING VARIABLE - Putri, Visakha Gautami; Viriany , Viriany (International Journal of Application on Economics and Business, 2023)
The-study aims to analyze the effect of profitability on capital structure and inflation as moderation variable on food.and.beverage company from.consumer_industry and listed in Indonesia Stock Exchange in_period 2019-2021. The sampling method is using purposive sampling technique and_the valid data was 24 and 72 data were processed. The data was processed_using_EViews 12 (software). The results is showing that profitability negatively influences capital structure and the inflation is proven to not able moderating the effect-of profitability-on_capital structure.